PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DEPARTEMEN HOUSEKEEPING DAN FRONT OFFICE DI HOTEL BOROBUDUR JAKARTA - Muhammad Rayyan; Bambang N.S (Human Capital Development, 2016)
Purpose- This study aim is to determine the motivation and work environment effect partially or simultaneously to work productivity in housekeeping and front office department at Borobudur Jakarta hotel. Design/methology/approach- The population in this study are employees in housekeeping and front office department at Borobudur Jakarta Hotel. the samples used in this study as many as 100 people. The sampling technique used was non probability sampling. Methods of data analysis used in this study is to test the validity, reliability test, classic assumption test (normality test, multicollinearity, heteroscedasticity test and linearity test). Findings- While testing the hypothesis includes the F-test, t test and partial correlation analysis and the coefficient of determination (R²). From the analysis it can be seen that Motivation variable and work environment variable has an influence on the work productivity either partially or simultaneously.